Tight Focusing of Partially Coherent Vortex Beams - Rakesh Kumar Singh (International Journal of Optics)
Tight focusing of partially polarized vortex beams has been studied. Compact form of the coherence matrix has been derived for polarized vortex beams. Effects of topological charge and polarization distribution of the incident beam on intensity distribution, degree of polarization, and coherence have been investigated.